The Challenge of Early Marriages in Zambia: An Exploration of the Actions of the Catholic Church (Hekima Review, 2016)
The paper qualitatively explores the response of the Catholic Church to earlynmarriages in Zambia using the media lens in order to mirror the public role of the Church in contemporary times. Document analysis (including media reports) supplemented with interviews were the main methods of data collection employed. Despite the voice of the Church on early marriages and interventions missing in scholarship in Zambia, the Church was fully involved in addressing the challenge of early marriages. The media portrayed the Church being called upon by the State to help end early marriages. Other actions of the Church were through advocacy, provision of information, empowerment programmes through skills training, and formal education. e argument is that the Catholic Church, guided by her social teachings was not only a mirror of society, but also a voice for the victims of the early marriages in contemporary Zambia.